2013
DOI: 10.1002/hyp.9808
|View full text |Cite
|
Sign up to set email alerts
|

From groundwater abstraction to vegetative response in fen ecosystems

Abstract: Hydrological effects of groundwater abstraction near a Danish river valley have been assessed by integrated hydrological modelling. The study site contains groundwater‐dependent terrestrial ecosystems in terms of fen and spring habitats that are highly dependent on regional and local scale hydrology. Fens are rare and threatened worldwide due to pressures from agriculture, to lack of appropriate management and to altered catchment hydrology. A solid foundation for hydrological modelling was established based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Pumping changes how regional flow discharges to riparian zones and streams (as streambed seepage, drainage, or groundwater-fed surface flow or springs). Johansen et al (2011Johansen et al ( , 2014 were the first studies on how groundwater seepage affects fen ecosystems (groundwater-dependent ecosystems). A pumping experiment in a shallow chalk aquifer showed that outflow through springs was reduced, while the shallow water table in the fen ecosystems was relatively unaffected (Johansen et al, 2011) and the effect on vegetation was minimal (Johansen et al, 2014).…”
Section: Early 2010smentioning
confidence: 99%
See 3 more Smart Citations
“…Pumping changes how regional flow discharges to riparian zones and streams (as streambed seepage, drainage, or groundwater-fed surface flow or springs). Johansen et al (2011Johansen et al ( , 2014 were the first studies on how groundwater seepage affects fen ecosystems (groundwater-dependent ecosystems). A pumping experiment in a shallow chalk aquifer showed that outflow through springs was reduced, while the shallow water table in the fen ecosystems was relatively unaffected (Johansen et al, 2011) and the effect on vegetation was minimal (Johansen et al, 2014).…”
Section: Early 2010smentioning
confidence: 99%
“…Johansen et al (2011Johansen et al ( , 2014 were the first studies on how groundwater seepage affects fen ecosystems (groundwater-dependent ecosystems). A pumping experiment in a shallow chalk aquifer showed that outflow through springs was reduced, while the shallow water table in the fen ecosystems was relatively unaffected (Johansen et al, 2011) and the effect on vegetation was minimal (Johansen et al, 2014). Many of these studies were supported by numerical modeling.…”
Section: Early 2010smentioning
confidence: 99%
See 2 more Smart Citations
“…The issue of the effect of rivers or lakes on the water relations in adjacent areas can be analysed through the application of hydrological mathematical models (Ha et al, 2008;Guay et al, 2013;Johansen et al, 2014;Mosley et al, 2014) or through statistical analyses (Aguilera et al, 2013;Sahoo and Jha, 2013;Varouchakis and Hristopulos, 2013).…”
Section: Introductionmentioning
confidence: 99%